Red LED Photobiomodulates the Metabolic Activity of Odontoblast-Like Cells - Almeida,Leopoldina de Fátima Dantas de (2016)
Abstract Phototherapy has been indicated as an adjunctive treatment for tissue repair, including the pulp tissue. However, there are no defined irradiation parameters, which is a great challenge to the clinical use of phototherapy. The aim of this study was to evaluate the effect of phototherapy with red LED on odontoblast-like MDPC-23 cells, using different parameter settings. Cells were seeded (104 cells/cm²), incubated for 12 h in complete DMEM and then the culture medium was replaced by DMEM supplemented with 0.5% FBS. After 12 h incubation, irradiations were performed (630±10 nm) using a LEDTable device with a 20 or 40 mW/cm² power density and 2 J/cm² energy dose. The cells were irradiated 1 or 3 times, at 1 min intervals. Non-irradiated cells served as control. The cells were evaluated for viability (MTT assay), total protein dosage (Lowry method) and number of viable cells (Trypan blue). The data (n=12 per group) were submitted to Kruskal-Wallis and Mann-Whitney tests (p=0.05). A single irradiation with 20 or 40 mW/cm² enhanced cell viability, which was negatively affected after 3 consecutive irradiations. Cells irradiated only once with 20 mW/cm² produced more proteins compared with those irradiated with 40 mW/cm². Reduction in the number of viable cells occurred only after 3 consecutive irradiations with 40 mW/cm². In conclusion, red LED was capable of biomodulating the metabolic activities of cultured MDPC-23 odontoblast-like cells. The best cell biostimulation was obtained when a single irradiation with 2 J/cm2 energy dose and 20 mW/cm2 power density was delivered to the pulp cells.